Does Biochar Improve Establishment of Tree Seedlings in Saline Sodic Soils?. (17th April 2015) - Drake, Jessica A.; Cavagnaro, Timothy R.; Cunningham, Shaun C.; Jackson, W. Roy; Patti, Antonio F.
Abstract: Reforestation of saline sodic soil is increasingly undertaken as a means of reclaiming otherwise unproductive agricultural land. Currently, restoration of degraded land is limited to species with high tolerances of salinity. Biochar application has the potential to improve physical, biological and chemical properties of these soils to allow establishment of a wider range of plants. In a glasshouse trial, we applied biochar made from Acacia pycnantha (5 Mg ha −1 ) or no biochar to either a low (ECe 4·75 dS m −1, ESP 6·9), a moderate (ECe 27·6 dS m −1, ESP 29·3) or a high (ECe 49·4 dS m −1, ESP 45·1) saline sodic soil. The regional common reforestation species Eucalyptus viminalis and Acacia mearnsii were planted as tubestock in to the soils. Early establishment indicators, including growth, plant condition and nutrition, were assessed at the end of a simulated growing season, 108 days after biochar application. Application of biochar increased height, and decreased root : shoot and the concentration of Mn, N and S in plants of E . viminalis when grown in the highly saline sodic soil. Biochar application increased the concentration of B in leaves of E . viminalis and increased the concentration of P, K and S in leaves of A . mearnsii when grown in the low saline sodic soil. The results confirm that there is potential for biochar to assist in reforestation of saline sodic soils. Copyright © 2015 John Wiley & Sons, Ltd.